Starazo triple switches – synthesis of unsymmetrical 1,3,5-tris(arylazo)benzenes - Andreas H. Heindl; Hermann A. Wegner (Beilstein Journal of Organic Chemistry, 2020)
Multistate switches allow to drastically increase the information storage capacity and complexity of smart materials. In this context, unsymmetrical 1,3,5-tris(arylazo)benzenes – ‘starazos’ – which merge three photoswitches on one benzene ring, were successfully prepared. Two different synthetic strategies, one based on Baeyer–Mills reactions and the other based on Pd-catalyzed coupling reactions of arylhydrazides and aryl halides, followed by oxidation, were investigated. The Pd-catalyzed route efficiently led to the target compounds, unsymmetrical tris(arylazo)benzenes. These triple switches were preliminarily characterized in terms of their isomerization behavior using UV–vis and 1H NMR spectroscopy. The efficient synthesis of this new class of unsymmetrical tris(arylazo)benzenes opened new avenues to novel multistate switching materials.